Testing the efficient market hypothesis with Indonesian Islamic Stocks during the Covid-19 pandemic - Tiara Early Afifah; Neneng Hasanah; Mohammad Iqbal Irfany (goodwood publishing, 2023)
Purpose: This study aims to identify the phenomenon of overreaction in Islamic stocks during the COVID-19 pandemic and understand how various pieces of information during the pandemic influenced investors to overreact, leading to market inefficiency. Research Methodology: This study employs two main methods: an event study focusing on the overreaction phenomenon in the Islamic stock market, and cross-sectional regression to analyze the factors that influence it. Results: Overreaction was observed in the winner's stock portfolio during the announcement of Indonesia's first COVID-19 case. However, during other significant events, such as the National Economic Recovery program issuance, the arrival of the vaccine, and the highest increase in daily positive cases, overreaction was seen in both the winner and loser stock portfolios. Factors such as abnormal returns, information leakage, and company ownership are identified as significant influencers of this overreaction. These factors were found to be negatively related to cumulative abnormal returns post-event, indicating their role in the overreaction phenomenon. Limitation: This study focuses on the overreaction phenomenon of Shariah stocks in the Jakarta Islamic Index (JII) during the COVID-19 pandemic in 10 selected events from October 1, 2019, to July 23, 2021. Contribution: This study offers insights into the behavior of Islamic stocks in Indonesia during the pandemic, helping stakeholders understand market inefficiencies during crises.